If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26x + 18 = 5(5x + 8) Reorder the terms: 18 + 26x = 5(5x + 8) Reorder the terms: 18 + 26x = 5(8 + 5x) 18 + 26x = (8 * 5 + 5x * 5) 18 + 26x = (40 + 25x) Solving 18 + 26x = 40 + 25x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25x' to each side of the equation. 18 + 26x + -25x = 40 + 25x + -25x Combine like terms: 26x + -25x = 1x 18 + 1x = 40 + 25x + -25x Combine like terms: 25x + -25x = 0 18 + 1x = 40 + 0 18 + 1x = 40 Add '-18' to each side of the equation. 18 + -18 + 1x = 40 + -18 Combine like terms: 18 + -18 = 0 0 + 1x = 40 + -18 1x = 40 + -18 Combine like terms: 40 + -18 = 22 1x = 22 Divide each side by '1'. x = 22 Simplifying x = 22
| 3(x-5)+2=5-(x+2) | | (-4-5i)(2+10i)= | | 7h-12=4h+3 | | 103/29 | | 3x(x+1)=22 | | X/37=19 | | -33/29 | | 2x-9x+8=x-8+16 | | 136-(58x)=-70 | | c=a(w/150) | | -1-1/2-1/3-1/4 | | 4x(x-4)(x-6)=0 | | x^2+x+1+3x^2+7x+39=180 | | (-7/3)x*-3 | | -27x=-12 | | -25-(-13)= | | 2.68d+2.04=-1.02+6.1 | | 5x-12-2=3x-14+2x | | 4x+20x-12=0 | | 58x-(136)=-70 | | 5+3x=29+5x-8x | | 4x-3/5=6 | | x-1+3=x^2 | | 11x+x=144 | | (58x)-136=-70 | | x^4+5x^2-7=0 | | 11-(-34)= | | 4a(4)=360 | | -3-9+x=89 | | 2x+37+60=x+97 | | 17x-12x-9=15-8-3x | | 2x-7+3x=4x-2 |